THE USE OF NEOLOGISMS IN CONTEMPORARY LITERATURE: A CASE STUDY OF THE BRIEF WONDROUS LIFE OF OSCAR WAO BY JUNOT DÍAZ - Ma’ripov Jalolxon Kamoliddin o’g’li; Eshbekova Laziza Xayrulla qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article delves into the innovative use of neologisms in contemporary literature, focusing on Junot Díaz’s Pulitzer Prize-winning novel, “The Brief Wondrous Life of Oscar Wao.” The work is notable for its rich linguistic tapestry that combines English, Spanish, and various cultural references, reflecting the complexities of the Dominican-American experience. Through the analysis of key neologisms such as "fukú," "nerd," and "ghetto," the article examines how these newly coined terms contribute to character development, cultural identity, and thematic depth within the narrative. The article posits that Díaz’s neologisms not only serve as tools for storytelling but also as cultural signifiers that encapsulate the struggles and aspirations